AKUT MİYOKARD İNFARKTUS HASTALARINDA SERUM İRİSİN DÜZEYLERİNİN VE GENETİK VARYANTLARININ ARAŞTIRILMASI - DİŞ, ÖZGE (Fırat Üniveristesi, 2017)
Amaç: Akut Miyokard İnfarktusu (AMI) Koroner Arter Hastalıklarının (KAH) en sık görülen tipidir. İrisin hormonu yeni keşfedilen FNDC5 geni tarafından kodlanan kalpta dahil kas ve yağ dokudan sentezlenen bir miyokindir. Çalışmamızda AMI hastalarının serum irisin düzeylerinin ve Türk toplumundaki genetik varyantların kontrolle karşılaştırılarak araştırılması amaçlanmıştır. Gereç ve Yöntem: Çalışmaya AMI tanısı alan 225 hasta ve 225 sağlıklı birey alındı. AMI sonrası ilk 12-24 içinde hasta ve kontrol bireylerinden kan örneği alınarak serumları ayrıldı. Serum irisin konsantrasyonları ELİSA ile ölçüldü. FNDC5 genindeki rs16835198, rs3480 ve rs726344 varyantları DNA izolasyonu sonrası RT-PCR ile genotiplendi. Bulgular: Serum irisin konsantrasyonlarının kontrolle karşılaştırıldığında hasta grubun da anlamlı düzeyde azaldığı belirlendi (p=0.001). FNDC5 genindeki rs16835198, rs3480 ve rs726344 genotip ve allel sıklıkları açısından hasta ve kontrol grubu arasında anlamlı bir farklılık bulunmadı. Ancak hasta grubu içinde hipertansiyonlu hastalarla kontrol grubu karşılaştırıldığında rs16835198 ve rs726344 varyant allellerinin hipertansiyonlu hastalarda anlamlı düzeyde arttığı belirlendi (p=0.00 ve p=0.00). Sonuç: Çalışmamız FNDC5 gen varyantlarının AMI hastalarında kontrolle karşılaştırılarak araştırıldığı ilk çalışmadır. FNDC5 gen varyantlarının ve irisin düzeylerinin AMI dahil KAH'ın etyopatogenezinde önemli roller oynadığı düşünülmektedir. Verilerimizin doğrulanması için daha geniş kapsamlı araştırmalara ihtiyaç vardır.

The investigation of serum irisin levels and genetic variants in patients with acute myocardial infarction. Objective: Acute myocardial infarction (AMI) is the most common type of coronary artery disease (CAD). The irisin hormone is synthesized from many tissue, including muscle, heart and fat tissue, which is encoded by FNDC5 gene. In our study, it was aimed to investigate the serum irisin concantrations of AMI patients and genetic variants in Turkish population by comparing with controls. Materials and Methods: 225 patients with AMI and 225 healthy subjects were included in the study. Blood samples were taken from patients in the first 12-24 hours after AMI and control subjects and sera were separated. Concentrations of serum irisin were measured with ELISA. Variants of rs16835198, rs3480 and rs726344 in the FNDC5 gene were genotyped by RT-PCR after genomic DNA isolation. Results: Concentrations of serum irisin were significantly decreased AMI patients as compared to control subjects (p =0.001). There were no significant differences between the patient and control groups in terms of genotype and allele frequencies of rs16835198, rs3480 and rs726344 in the FNDC5 gene. However, in patients with hypertension compared with controls subjects, the rs16835198 and rs726344 variant alleles were significantly increased in patients with hypertension (p =0.00 and p =0.00 respectively). Conclusions: To the best of our knowledge, it is the first study to investigate a relationship between FNDC5 gene variant and AMI. compared with controls in AMI patients. Our data suggested that irisin contributed to an earlier detection for AMI. Therefore, serum irisin concentrations can serve as a novel biological marker for early diagnosis of AMI. More extensive research is needed to verify of our data.
The investigation of serum irisin levels and genetic variants in patients with acute myocardial i?nfarction
Keywords: Moleküler Tıp